2015
DOI: 10.1038/srep13324
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the interaction of VP1 with GM130 which may implicate in the pathogenesis of CVB3-induced acute pancreatitis

Abstract: Coxsackievirus B3 (CVB3) is a causative agent of viral myocarditis, pancreatitis, and meningitis in humans. Although the susceptibility of CVB3-induced acute pancreatitis is age-dependent, the underlying mechanisms remain unclear. Here we identified the host factor Golgi matrix protein 130 (GM130) as a novel target of CVB3 during CVB3-induced acute pancreatitis. The viral protein VP1 interacted with GM130, disrupted GM130-GRASP65 complexes, and caused GM130 degradation, which may lead to disruption of the Golg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…To further investigate whether the inhibitory effect of miRNA-21 on progeny release was due to suppressed CVB3 replication, we detected viral capsid protein VP1 expression as well as the viral load within infected Hela cells [36, 37]. No significant change in VP1 expression and viral load was observed between infected cells overexpressing miRNA-21 and control miRNA, suggesting that miRNA-21 might not affect CVB3 replication in infected cells at least within 24 h post infection.…”
Section: Discussionmentioning
confidence: 99%
“…To further investigate whether the inhibitory effect of miRNA-21 on progeny release was due to suppressed CVB3 replication, we detected viral capsid protein VP1 expression as well as the viral load within infected Hela cells [36, 37]. No significant change in VP1 expression and viral load was observed between infected cells overexpressing miRNA-21 and control miRNA, suggesting that miRNA-21 might not affect CVB3 replication in infected cells at least within 24 h post infection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, interrogation of the CVB3-DAF (human decay-accelerating factor) complex structure, determined by cryo-electron microscopy, confirmed that DAF S104 is an essential site for close contact with VP1 residue T271 during CVB3 invasion [10][11][12][13]. Our previous work also identified Golgi Matrix Protein 130 (GM130) as a direct intracellular target of CVB3 VP1, and indicated that the interaction between VP1 and GM130 could disrupt the structure of the Golgi ribbon [14]. However, few studies have reported the effects of VP1 on cell proliferation and its direct protein targets in cells.…”
Section: Introductionmentioning
confidence: 53%
“…An in vitro protein-protein binding assay was performed as previously described [14]. pGBKT7-VP1 bait vector and pGADT7-MAT1 prey vector were used as templates to transcribe and translate in vitro, then labeled with 35…”
Section: Protein-protein Binding Assay In Vitromentioning
confidence: 99%
“…In addition, interrogation of the CVB3-DAF (human decay-accelerating factor) complex structure, determined by cryo-electron microscopy, confirmed that DAF S104 is an essential site for close contact with VP1 residue T271 during CVB3 invasion [ 12 , 13 ]. Our previous work also identified Golgi Matrix Protein 130 (GM130) as a direct intracellular target of CVB3 VP1, and indicated that the interaction between VP1 and GM130 could disrupt the structure of the Golgi ribbon [ 14 ]. However, few studies have reported the effects of VP1 on cell proliferation and its direct protein targets in cells.…”
Section: Introductionmentioning
confidence: 99%